How Persian Oak (Quercus brantii) Copes with Crown Dieback: A Biochemical Perspective - Iranmanesh, Yaghoub; Mehrabi, Ali Ashraf; Jahanbazi, Hassan; Pourhashemi, Mehdi; Shariat, Anahita; Zarafshar, Mehrdad (Forest science and technology, 2025)
Crown dieback of oak is a critical issue in arid and semi-arid regions, threatening forest sustainability and biodiversity. This study explores the biochemical responses of Persian oak trees under varying health conditions to uncover the mechanisms driving oak decline. Key parameters such as photosynthetic pigments, antioxidant enzyme activities, osmolyte accumulation, and oxidative stress markers were analyzed. Despite stable photosynthetic pigments in both healthy and declining trees, catalase and peroxidase antioxidant enzyme levels were significantly higher in declining trees, highlighting their role in mitigating oxidative damage. Proline accumulation emerged as a vital osmoprotectant, while malondialdehyde (MDA) levels reflected heightened lipid peroxidation and oxidative stress. Principal Component Analysis (PCA) further differentiated healthy and declining trees, identifying antioxidant activity as a significant factor. These findings provide valuable insights into Persian oak resilience, offering a foundation for early detection of decline and sustainable management practices to mitigate the effects of climate change on oak forests.